2007
DOI: 10.1111/j.1365-2141.2006.06464.x
|View full text |Cite
|
Sign up to set email alerts
|

Modern management of non‐Hodgkin lymphoma in HIV‐infected patients

Abstract: SummaryPatients infected with human immunodeficiency virus (HIV) are at greater risk of developing non-Hodgkin lymphoma than the general population and aggressive B-cell lymphoma has become one of the most common of the initial acquired immunodeficiency syndrome (AIDS)-defining illnesses. This review considers the prognostic factors and new approaches to the treatment of patients with AIDS-related lymphoma (ARL). As highly active antiretroviral therapy (HAART) became available, the survival of many ARL patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 87 publications
1
27
0
1
Order By: Relevance
“…In general, studies have shown early introduction of HAART therapy to be associated with superior outcomes, which has allowed for the administration of more dose-intense regimens and a reduction in treatment-associated toxicity. 126,127 In the NHL HIV 93 trial of risk-adapted intensive chemotherapy in patients with ARL, Mounier et al 128 reported that HIV score, IPI (international prognostic index) score, and HAART affect survival in patients with ARL but not the intensity of the chemotherapy. Combination chemotherapy regimens such as CHOP or CDE (cyclophosphamide, doxorubicin, and etoposide) given with concomitant HAART, [129][130][131] or the EPOCH regimen given without HAART, 132 have been proven effective and tolerable in patients with ARL.…”
Section: Treatmentmentioning
confidence: 99%
“…In general, studies have shown early introduction of HAART therapy to be associated with superior outcomes, which has allowed for the administration of more dose-intense regimens and a reduction in treatment-associated toxicity. 126,127 In the NHL HIV 93 trial of risk-adapted intensive chemotherapy in patients with ARL, Mounier et al 128 reported that HIV score, IPI (international prognostic index) score, and HAART affect survival in patients with ARL but not the intensity of the chemotherapy. Combination chemotherapy regimens such as CHOP or CDE (cyclophosphamide, doxorubicin, and etoposide) given with concomitant HAART, [129][130][131] or the EPOCH regimen given without HAART, 132 have been proven effective and tolerable in patients with ARL.…”
Section: Treatmentmentioning
confidence: 99%
“…Neg (1) IgM-λ (7) Absent (8) 1:10,240 (2) P (4) 1:5,120 (9) C ( Absent (4) 1:20,480 (2) P (3) 1:5,120 (12) C (12) was slightly higher than that for 72 patients without MG/ OG (29:43), the differences were not statistically significant ( P = 0.60). The median age (68 years, range = 33-80 years) of patients with MG/OG was not significantly different ( P = 0.82) from that of patients without MG/OG (67 years, range = 24-88 years).…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Furthermore, certain pathogens, such as human immunodeficiency virus (HIV) or hepatitis C virus, show not only a transient pattern but also a persistent pattern of MG or OG and are associated with B cell malignancies. [9][10][11][12][13][14][15][16] In this context, a finding of MG or OG in certain infectious diseases requires more invasive tests to identify the underlying progress. In this study, we serially monitored peripheral blood samples for MG or OG after treatment of the infection rather than bone marrow examination during the acute or early convalescent phases to avoid any possible confusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, since recommendations are based on case reports or small case series, there is no defined standard treatment for this rare and clinically heterogeneous disease. 3,4 Recent reports suggest treatment of MCD with monoclonal anti-CD20 antibody rituximab due to detection of CD20 in mantlezone lymphoid cells from lymph nodes of HHV-8 related MCD. Especially, the combination of CHOP (cyclophosphamide, doxorubicin, vincristine and prednisone) with rituximab showed remission with lower relapse rates compared with CHOP alone.…”
Section: -3 MCD Occursmentioning
confidence: 99%